Isolasi Dan Identifikasi Senyawa Minyak Atsiri Daun Gamal (Gliricidia sepium [Jacq] Walp) - Rahmiyani, Ira (Jurnal Farmasi Udayana; Spesial Issue, Desember 2020DO - 10.24843/JFU.2020.v09.i03.p01, 2020)
Essential oils are one group of secondary metabolites that are mostly found in the tissues of plants. Gliricidia leaves can produce essential oils that are used as anti-bacterial and anti-scabies. The purpose of this study to determine the constituents of essential oil compounds in the leaves of Gliricidia. The method used distillation water vapor and analyze with gas chromatography mass spektroscopy (GC-MS). The results showed that the Gliricidia leaves contains 100 components of essential oil compounds and 3 major components of essential oil compounds as follows:2-Pentadecanone, 6,10,14-trimethyl- (CAS) 6,10,14-Trimethyl-2-pentadecanone 20.07%, 2-Hexadecen-1-ol, 3,7,11,15-tetramethyl-, [R- [R *, R * - (E)]] - (CAS) Phytol 13.55%, a 1.2-Benzenedicarboxylic acid, bis (2-ethylhexyl) ester (CAS) - bis (2-ethylhexyl) phthalate 10,11%. Keywords: Gliricidia leaves, essential oil, gas chromatography mass spectroscopy (GC-MS).